A hypercomplex method for solving piecewise continuous biharmonic problem in domains with corner points - Gryshchuk, S.; Plaksa, S. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.54, 517.95We consider a piecewise continuous biharmonic problem in domains with corner points and the corresponding Schwarz-type boundary-value problem for monogenic functions in a commutative biharmonic algebra. A method for reducing the problems to a system of integral equations is developed.